Jednolity europejski rynek zamówień publicznych szansą dla polskich przedsiębiorstw? - Starzyńska, Wacława (Is Single European Public Procurement Market a Chance for Polish Enterprises?, 2006)
Public procurements in the European Union are an important instrument of creating demand from one side, and state intervention from the other. Public procurements are more or less internationalized. The Polish law connected with public procurement is fully harmonized with nine European Union directives. Special attention in the European Union is paid to removing national preferences in public procurement procedures. The paper tries to estimate the size and the structure of public procurement in Poland and in the European Union countries focusing on central and local government expenditure. Public procurement market in the European Union is open for entities, however, small and medium enterprises are still not sufficiently competitive in this field in comparison with big firms. Joining the European Union Poland creates the same conditions for foreign enterprises. On the other hand, the Polish firms may apply for public procurement contracts in other European countries. In the paper advantages of the single European market are presented in the context of future public procurement.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1109, s. 555-568